القىاعد الفقهية وتطبيقاتها عند الإمام الفندلاوي من خلال كتابه "تهذيب المسالك - دردوري, فاطمة الزهراء; - زغوان, ليلى; - قاسمي, مريم (University of Eloued-جامعة الوادي, 2016)
يتناول ىذا البحث، موضوع القواعد الفقيية وتطبيقاتيا عند الإمام الفندلاوي من خلال كتابو )تيذيب المسالك(، ومحتواه يشمل أربعة مباحث: ثلاثة مباحث نظرية، الأول والثاني خصصناىما لمتعريف بالمؤلِّف والمؤلَّف، والثالث تناولنا فيو مفيوم القواعد الفقيية، ومبحث تطبيقي اخترنا فيو مجموعة من القواعد الفقيية من أبواب مختمفة من أبواب ىذا الكتاب، وكل قاعدة نذكر ليا صيغ أخرى لتقريب معناىا وخاصة أ ن الفندلاوي لا يص رح أحيانا بمفظ القاعدة المتعارف عميو، وبعدىا نعطي معناً إجماليا لمقاعدة وبيان نوعيا بكونيا قاعدة كمية أو فرعية وما إلى ذلك، ونعقبيا بذكر المسألة التي أوردىا الفندلاوي عمى ىذه القاعدة وبيان أ ري مذىبو وآ ا رء أئمة المذاىب الأخرى. ثم ختمنا بحثنا بخاتمة تمم أىم النتائج المتوصل إلييا خلال د ا رستنا وبعض التوصيات Abstract This research is devoted to study the subject and application of jurisprudential rules at the Imam Fandalaoui through his book "tahdeeb el massalek" (edifying ways) which contains of four chapters. Two of the three theoretical chapters are dedicated to define the author and his book, the third chapter studies the concept of jurisprudential rules. Moreover, a practical chapter in which we had selected different rules from different rubrics in that book, hence we gave other modes to each rule in order to clarify its meaning; particularly that the Imam Fandalaoui rarely profess the name of rules. After all, we give an overall meaning, type of each rule whether it was a total or a secondary rule....etc. then we study the issue that the Imam posits about each rule comparing his opinions with other doctrines views. Finally, a conclusion of the most important outcomes with some recommendations.
مذكرة ليسانس
Keywords: القواعد الفقهية/الفندلاوي /"تهذيب المسالك; Règles jurisprudentielles / Al-Fandalawi / « Tahdheeb Al-Masalik ».